O humor e a crítica em Hagar, o Horrível, de Dik Browne, no Jornal Folha de São Paulo (1973-1974) - Costa, Fabio Antonio (2013)
This study intends to examine the series of comic strips Hagar, the Horrible created in 1973 by American designer Dik Browne, being analyzed the universe of 200 strips components from the first year of publication by the newspaper Folha de São Paulo, highlighting some sequences which best fit to the subjects explored. We deepened how this comic through its multiple features and form of language, developed a conception of the world by deconstructing ideas and discourses, valuing other human manifestations and social groups not very evident in the troubled 1970s in the United States. We also work some categories of analysis, such as humor, art, daily life, comics, culture, among others, in their ensemble contribute to a better understanding about the potential of Hagar, character embedded in a meaningful critique of the events and ideas of that conjuncture, to build a rich universe of possibilities and reflection of the world